Methods of creating an ironic style in crosswords language (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
The article deals with the peculiarities of the linguistic means of the modern crosswords. The different methods of the linguistic game are represented in this article. The most important among them are: polysemy, paronomasia, phraseological unit, precedent phenomena, word-forming means etc.
Keywords: crossword; humorous style; ironic style; language game; polysemy; pun; paronomaziya; idioms; precedent phenomenon